Analyzing Influencing Factors of Uterine Rupture in Pregnant Women with Scarred Uterus Undergoing Repeat Delivery and Evaluating the Predictive Value of Lower Uterine Anterior Wall Thickness - Zhang L; Li T; Zhang P; Li C (International Journal of Women's Health)
Liying Zhang,1,* Ting Li,1,* Pengming Zhang,1 Chunjuan Li2 1Department of Ultrasound Medicine, Zhangjiakou First Hospital, Zhangjiakou, Hebei Province, 075000, People’s Republic of China; 2Department of Obstetrics and Gynecology, Chongli Hospital, Peking University Third Hospital, Beijing, 076350, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ting Li, Email tgps643@163.comObjective: To analyze influencing factors of uterine rupture in pregnant women with a scarred uterus undergoing repeat delivery and to investigate the predictive value of transabdominal ultrasound measurement of lower uterine anterior wall thickness.Methods: A retrospective analysis of 159 pregnant women with scarred uterus (March 2022–May 2024) divided into rupture group (n=48) and non-rupture group (n=111). Lower uterine anterior wall thickness was measured via transabdominal ultrasound pre-delivery. Univariate/multivariate logistic regression and ROC curves were used to identify risk factors and evaluate predictive performance.Results: The rupture group had higher rates of advanced maternal age, prenatal BMI ≥ 30 kg/m², multiparity, single-layer cesarean suturing, and shorter inter-pregnancy intervals (all P< 0.05). Lower uterine anterior wall thickness was significantly thinner in the rupture group (1.24± 0.31 mm vs 2.19± 0.52 mm, P< 0.001). Multivariate analysis identified thinner lower uterine anterior wall thickness (OR=2.359, 95% CI:1.362– 4.134) and single-layer suturing (OR=1.863, 95% CI:1.125– 3.086) as independent risk factors, while longer inter-pregnancy interval was protective (OR=0.256, 95% CI:0.091– 0.634; all P< 0.05). ROC analysis showed AUCs of 0.821 (scar thickness), 0.783 (single-layer suturing), and 0.759 (inter-pregnancy interval); combined prediction achieved an AUC of 0.894 (95% CI:0.837– 0.946), sensitivity 90.23%, specificity 84.15%. Uterine rupture was associated with worse perioperative outcomes (eg, higher transfusion rates, longer hospitalization) and adverse neonatal outcomes (lower birth weight, more preterm births; all P< 0.05).Conclusion: Lower uterine anterior wall thickness, single-layer suturing, and inter-pregnancy interval are key determinants of uterine rupture. Combined assessment of these factors provides high predictive accuracy (AUC=0.894) and improves risk stratification.Keywords: lower uterine anterior wall thickness, scarred uterus, uterine rupture, risk factors, predictive value